Balanço de água no ciclo da cultura de soja: representação no modelo de vegetação dinâmica Agro-IBIS - Moreira, Virnei Silva (2012)
Exchanges of water in the soil-plant-atmosphere are controlled by physical-hydric soils, which in turn are highly variable in space and very sensitive to the use and soil management, especially in an agroecosystem. Precipitation, runoff, soil water storage and exchange of water vapor between the surface-atmosphere obtained from the eddy covariance and hydro-physical properties of soil were analyzed during the growing season (2009/2010) for no-till systems (NT) and conventional tillage (PC) in the cycle of soybean, in Cruz Alta, northwest of Rio Grande do Sul (RS). Most models that describe the interaction biosphere - atmosphere in agroecosystems has not efficiently represent physical differences for different soil management. In this sense, the study also will examine the response of the dynamic exchanges of water in the Agro-IBIS model when the soil physical properties in a system of management of PD (without revolution planting soil) and PC (with planting soil Revolution) are implemented. For this purpose, are used to soil properties of a long-term experiment in southern Brazil 2009/2010. Moreover, mathematical adjustments in leaf area index (LAI) is suggested to better represent the stage of leaf senescence. The results of the dynamics of soil water and evapotranspiration in the Agro-IBIS model for soybeans, when the implementation of soil properties and setting the IAF are compared with experimental data and with a simulation in which the soil property are described through the global database. The model represents satisfactorily the dynamics of soil water and evapotranspiration for both management systems, especially for wet periods. The results presented for the conventional management system are best correlated with the simulations, when the physical properties of this system are implemented and leaf senescence is corrected. Of the major changes that have been added, such as setting physical properties of soil, definition of the retention curve coefficients, and phenology of the crop, the main one was the consideration of a new factor of decline in leaf area index during senescence which greatly reduced the error in water balance components of the surface of soybean.